Pandemic elevates sensitivity to moral disgust but not pathogen disgust - Schwambergová, Dagmar; Kaňková, Šárka; Třebická Fialová, Jitka; Hlaváčová, Jana; Havlíček, Jan (Scientific reports, 2023)
The behavioral immune system, with disgust as its motivational part, serves as the first line of defense in organisms' protection against pathogens. Laboratory studies indicate that disgust sensitivity adaptively adjusts to simulated environmental threat, but whether disgust levels similarly change in response to real-life threats, such as a pandemic, remains largely unknown. In a preregistered within-subject study, we tested whether the threat posed by the Covid-19 pandemic would lead to increased perceived disgust. The perception of threat was induced by testing during two phases of the Covid-19 pandemic (periods of high vs. low pathogen threat). We found heightened levels of moral disgust during a "wave" of the pandemic, but the effect was not observed in the domain of pathogen or sexual disgust. Moreover, the age of respondents and levels of trait anxiety were positively associated with pathogen and moral disgust, suggesting that variation in disgust sensitivity may be based chiefly on stable characteristics.
Keywords: Morals; Emotions; Disgust; Pandemics; emoce; lidé; pandemie; Humans; mravy; COVID-19; odpor